Sedimentation Characteristics and Retention Ratio Calculation of Dredged Soil - Roh, Yong Eun; Kim, Gi Yun; You, Min Ku; Chang, Ilhan (Geotechnical Special Publication, 2024)
Retention rate refers to the content of soil remaining in the dumped area compared to the left sample during dredged soil dumping. During reclamation construction, the retention rate calculates the amount of dredged soil, so it is essential to determine the exact retention rate. The retention rate may be calculated differently depending on the soil characteristics, but currently, in the case of dredging and reclamation on the West Coast, the retention rate is empirically applied at 70%–95%, or the amount of dredged soil is calculated through examples of application of retention rates in similar districts nearby. Accordingly, in this study, to accurately calculate the retention rate, a separate sedimentation model test was conducted using dredged soil at the location where the actual project was carried out. Separated sedimentation characteristics were confirmed through mechanical and physical tests for each deposition distance, and the retention rate was calculated to be 89.0%, which is relatively higher than the literature and existing cases. This study was used as primary data to confirm the feasibility of the road construction project connecting the Saemangeum area to the north and south.
Keywords: Characteristic ratio; Dredged soils; Mechanical; Model tests; Retention rate; Retention ratio; Sedimentation characteristic; Sedimentation model; Soil characteristics; West coast